Intracranial aneurysm as extra-renal manifestation of polycystic kidney disease – A case report - Rabrenović, Violeta; Ćulafić, Slobodan; Rabrenović, Milorad; Dragović, Tamara; Trešnjić, Saša; Mašić, Siniša; Matunović, Radomir; Ignjatović, Ljiljana; Antić, Svetlana; Petrović, Milica; Pilčević, Dejan; Rakonjac, Aleksandar; et al. (Vojnosanitetski pregled, 2020)
Introduction: Polycystic kidney disease is a hereditary kidney disease characterized by the occurrence of cysts (fluid-filled enlargement) in the cortex or medula of the kidney, and is inherited in an autosomal dominant or autosomal recessive. In addition to multiple cysts in the kidneys, there may be as many extra-renal manifestations (cysts of the liver, pancreas, lungs, heart, etc.), among which the most serious occurrence of intracranial aneurysms.Case report: A 57 year old female  patient with polycystic kidney disease and stage III renal failure was hospitalized  in our clinic  due to  decreased  renal function, the development of urinary tract infections, headaches, and  unregulated blood pressure, despite the usual treatment.  This patient also had a number of associated diseases: obesity, diabetes mellitus (the insulin-dependent type), hypothyroidism, and depression syndrome. After better regulation of blood pressure, resolved urinary tract infections, and improved renal function, there were still persistent headaches (resulting in the excessive use of analgesics), but with adequate preparation, MSCT angiography of blood vessels of the  head was performed. As a  result,  we diagnosed the saccular intracranial aneurysm (IA) with  anterior localization. Given the symptoms, age and comorbidity, digital subtraction angiography was performed, and showed IA (5,2 mm x 4 mm), saccular with wide neck, affecting both branches MCA. During the procedure the stent was placed, which filled the aneurysm with spirals, cutting it off from circulation. After the successful procedure, and without further complications, the patient no longer had headaches, and blood pressure was maintained within the required limits, with stable parameters of chronic renal failure.Conclusion: The case of the patient with polycystic kidney disease, stage III chronic renal failure, with a number of comorbidities (headache, obesity, hypertension, diabetes mellitus, hypothyroidism) and diagnosed with symptomatic intracranial aneurysm was successfully solved with a multidisciplinary approach, emphasizing the importance of teamwork in daily practice.
Keywords: polycystic kidney disease; kidney failure, chronic; intracranial aneurysm; diagnosis; angiography, digital subtraction; stents; treatment outcome.